Smart cities should also make people skilled : Experts - (:unkn) unknown (Hindustan Times, 2014)
The opening ceremony of ‘Samavesh’ the 16th National Convention of National Organisation of Students of Planning hosted by SPA, Bhopal was inaugurated on Friday by Padma Bhushan M. N. Buch, former city planner and retired bureaucrat, key-note address delivered by Prof. Amitabh Kundu, Ex-Prof. JNU, Delhi and welcome address delivered by Padma Shri awardees Prof. V. K. Singh, Director SPA , Bhopal. Convention will comprise various activities including both academic and non-academic.
Keywords: 16th convention of NOSPlan; Smart City; SPA Bhopal Convention 2014; City Planning; Samvesh-16th annual NOSPlan Convention 2014